IN-GOOD-NEWS-IA”: THE ROLE OF GOOD NEWS FROM INDONESIA (GNFI) IN HELPING TO ENGENDER SENSE OF NATIONHOOD - Evelynd Evelynd; Sri Oktika Amran; Muhammad David Hendra (Jurnal Ranah Komunikasi, 2023)
The bad news seemed to have become a daily dish in a variety of Indonesian media today. Meanwhile, positive news and impressive achievements of Indonesia are often masked, or only displayed in a tiny part of the whole story. It also dismisses the sense of concern for a nation because the audience is fed up. News reporting has the possibility to influence public opinion and audience behaviour. Furthermore, the effects may have an impact on the sense of nationhood. The matters about a country are reflecting on how the media plays the role as news platform in creating the values of nationalism in the content. This essay examines the roles of Good News From Indonesia (GNFI) news platform and social media movement in Indonesia in helping to engender a sense of nationhood. This research uses qualitative methods, including media observation, in-depth interview, and also completed with literature review to acquire data to support the analysis. The essay focuses on three primary roles of GNFI, which are fulfilling the needs of useful information, restoring the optimism of Indonesia, and rebuilding confidence and citizen’s optimism.